2012
DOI: 10.1124/mol.112.081372
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Inhibits Voltage-Activated Ca2+ Channels in Vitro: Mechanisms and Structural Requirements

Abstract: ABSTRACT-hybridized carbon atom between the two aromatic rings and 2) the two aromatic moieties in angulated orientation are optimal for BPA's effectiveness. Since BPA highly pollutes the environment and is incorporated into the human organism, our data may provide a basis for future studies relevant for human health and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 46 publications
4
47
0
1
Order By: Relevance
“…It states that estrogens act by binding directly on parts of ion channels. It was based mostly on precise single-channel recordings (mostly from excised inside-out patches, see references in Table 4), but also on other methods, such as binding studies [1-3], site mutations [4], pharmacological and biophysical analysis [5], kinetics of estrogen effects [6], etc. Results from such studies are presented in Table 4.…”
Section: Direct Rapid Estrogen Actions On Ion Channelsmentioning
confidence: 99%
“…It states that estrogens act by binding directly on parts of ion channels. It was based mostly on precise single-channel recordings (mostly from excised inside-out patches, see references in Table 4), but also on other methods, such as binding studies [1-3], site mutations [4], pharmacological and biophysical analysis [5], kinetics of estrogen effects [6], etc. Results from such studies are presented in Table 4.…”
Section: Direct Rapid Estrogen Actions On Ion Channelsmentioning
confidence: 99%
“…The blockade of hNa v 1.5 by BPA had similar properties as that by local anesthetics; the two share a common binding site on hNa v 1.5 involving amino acid F1760. Later, Deutschmann et al reported that BPA inhibited the L-type Ca 2+ channels in isolated mouse ventricular myocytes in a dose-dependent manner with an IC 50 of 2.5 × 10 −5 M [62]. The blockade was fully reversible, and BPA likely exerted its action by binding to channels at the resting state.…”
Section: Impact Of Bpa On the CV System—experimental Studiesmentioning
confidence: 99%
“…An electrophysiological study has reported that Ca 2+ currents through native L-, N-, P/Q-, T-type Ca 2+ channels in rat endocrine GH3 cells, mouse dorsal root ganglion neurons or cardiac myocytes, and recombinant human R-type Ca 2+ channels expressed in HEK cells, were rapidly and reversibly inhibited by high doses of BPA with similar potency (EC 50 values: 26-35 µM), acting directly on the channel protein [33]. In another study, the mRNA expression of an auxiliary subunit of the high threshold voltage-gated Ca 2+ channel, Cacnα2δ2, was decreased in the left ventricle of male mice with low doses of BPA (1 nM) [26].…”
Section: Bpa Actions Onmentioning
confidence: 99%